Sweep ebook The story of a girl and her monster. - Auxier, Jonathan (2018)
For nearly a century, Victorian London relied on "climbing boys"—orphans owned by chimney sweeps—to clean flues and protect homes from fire. The work was hard, thankless, and brutally dangerous. Eleven-year-old Nan Sparrow is quite possibly the best climber who ever lived—and a girl . With her wits and will, she's managed to beat the deadly odds time and time again. But when Nan gets stuck in a deadly chimney fire, she fears her time has come. Instead, she wakes to find herself in an abandoned attic. And she is not alone. Huddled in the corner is a mysterious creature—a golem —made from ash and coal. This is the creature that saved her from the fire. Sweep is the story of a girl and her monster. Together, these two outcasts carve out a life—saving one another in the process. By one of today's most powerful storytellers, Sweep is a heartrending adventure about the everlasting gifts of friendship and hope.